Effect of storage period on different seed viability parameters in rajmash (Phaseolus vulgaris) - LAMICHANEY, AMRIT; PARIHAR, ASHOK KUMAR; KATIYAR, PARDIP KUMAR; SINGH, ANIL KUMAR; DIXIT, SHALINI; GUPTA, SANJEEV; SINGH, N P (The Indian Journal of Agricultural Sciences, 2021)
Seed longevity mainly depends on initial seed quality and storage conditions therefore; farmers and gene bank curators need to be aware of the storage potential of rajmash cultivars that contribute to the production of high quality seed during routine germplasm regeneration/multiplication. Consequently, it is important to generate information on seed longevity of rajmash. In the present investigation, 14 high yielding rajmash cultivars were stored for 4 years and periodical germination percent, time to initiate germination (t1), time to achieve 50% germination (t50) and uniformity of germination (U7525; time between 25 and 75 % germination) were recorded. The varieties exhibited the mean germination percentage of 93, 93, 73, 3 and 0.9 when stored for 0, 1, 2, 3 and 4 years, respectively. The results demonstrated that, all the 14 varieties could be safely stored for a minimum period of 1 year at ambient condition. Seven varieties (Arka Komal, IPR 98-5, IPR 98-3-1, HUR 137, HUR 203, HPR 35, Gujarat Rajmash 1) could be stored for 2 years as they demonstrated more than the minimum germination requirement (75%) of Indian Minimum Seed Certification Standard. Storing seeds for extended period not only decreased the final germination percentage, but also increased the time for t1, t50 and t7525, suggesting that use of aged seeds could result into poor field establishment coupled with delayed and non-uniform germination.